CLINICAL AND TYMPANOMETRIC ASSESSMENT OF MIDDLE EAR EFFUSION VERSUS MYRINGOTOMY FINDING - Mohammed, Hamed M.; Musa Bader, Hani; Fatoohi, Mazin N.; Ahmed, Mohamed D. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: The present study was planned to show the accuracy of clinical examination and tympanometry in diagnosis of middle ear effusion. Patients and Methods: The study involved 80 patients (160 ears )suspected to have otitis media with effusion (OME) from different age groups ; 56 were males and 24 were females . Clinical assessment for all patients included otoscopy , pneumatic otoscopy and audiological assessment by using pure tone audiometry and tympanometry then comparing the results to findings at myringotomy as the gold standard for presence or absence of fluid in the middle ear. Results : Fluid whether serous or glue was found in 100 ears ( 62.5 %) where as sixty ears were dry, sensitivity , specificity and accuracy of tympanometry were 90 % , 70 % and 85 % respectively , and for clinical assessment were 82 % , 52% and 71 % respectively . A combined clinical and tympanometry sensitivity and specificity were calculated and found to be 96 % and 92 % respectively. Conclusion : clinical examination as a method for diagnosis of middle ear effusion depend on experience of the examiner . tympanometry proved to be a reliable diagnostic tool for the diagnosis of OME , it appeared significantly better at determining non effusion state.